Management of patients with valvular heart disease : ACC/AHA pocket guideline : based on the ACC/AHA 2006 guideline revision - Bonow, Robert O.; Carabello, Blase A.; Chaterjee, Kanu; Leon, Antonio C. de, jr; Faxon, David P.; Freed, Michael D.; Gaasch, William H.; Lytle, Bruce Whitney; Nishimura, Rick A.; O'Gara, Patrick T.; O'Rourke, Robert A.; Otto, Catherine M.; et al. (s.n., 2006)
Valvular heart disease is one of several cardiac disorders that affect a large number of people who require diagnostic procedures and long-term management. The Pocket Guideline for Management of Patients With Valvular Heart Disease provides rapid prompts for 3 specific aspects of the management of patients with valvular heart disease. The pocket guide is derived from the full text of the ACC/AHA 2006 Guidelines for the Management of Patients With Valvular Heart Disease. These guidelines were first published in 1998 and then revised in 2006. The full-text guidelines provide a more detailed explanation of the management of valvular heart disease, along with appropriate caveats and levels of evidence.